(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2026)
This study was carried out to assess the levels of heavy metal contamination in giblets sourced from local restaurants in Southeastern Nigeria. The research employed atomic absorption spectrophotometry (AAS) for heavy metal analysis, followed by health risk assessments. The results revealed that copper (Cu) had the highest concentration among the metals detected, with a peak value (1.89 mg/kg) seen in the beef from Ishiagu, while cobalt (Co) had the lowest concentration, recorded at 0.02 mg/kg in the beef from Leru. In the Liver, iron (Fe) was the most abundant metal, with a maximum concentration (1.12 mg/kg) in Ishiagu, whereas arsenic (As) and lead (Pb) had the lowest concentrations (0.01 mg/kg) in Leru. The EDI analysis showed that Cu had the highest daily intake value (3.1002 × 10⁻³ and 2.8598 × 10⁻³ mg/kg/day) in the beef from Leru and Nkalagu, respectively, while Pb and As recorded the lowest EDI (1.86 × 10⁻⁵ and 3.71 × 10⁻⁵ mg/kg/day) in the Liver and Gizzard, respectively, across all locations. The THQ values indicated that Cu posed the highest non-carcinogenic risk, with a THQ (6.2004 × 10⁻²) in the beef from Leru, while Co had the lowest THQ (1.114 × 10⁻⁴) seen in the Liver .The HI values exceeded the safety threshold of 1 in Ishiagu, with a total HI of 1.1574, while the lowest HI was recorded in Nkalagu (5.84 × 10⁻¹). The CR analysis showed that nickel (Ni) had the highest carcinogenic risk, with a peak CR of 2.8412 × 10⁻³ in the beef from Nkalagu, whereas arsenic (As) had the lowest CR (1.58 × 10⁻⁷) in the Liver from Leru. Based on these findings, stricter monitoring and control measures are recommended to reduce heavy metal contamination in poultry products, ensuring food safety and protecting public health.